Phytochelatins: Key regulator against heavy metal toxicity in plants - Faizan, Mohammad; Alam, Pravej; Hussain, Anjuman; Karabulut, Fadime; Tonny, Sadia Haque; Cheng, Shi Hui; Hayat, Shamsul (Elsevier, 2024)
In recent years, heavy metals (HMs) attain lot of consideration due to their toxic nature in the environment. Natural as well as anthropogenic activities like urbanization & industrialization, use of fertilizers, and waste management contamination increased HMs exposure to living organisms. Due to continuous encountering with HMs, plants facing oxidative stress, nutritional imbalance, metabolic disturbance and yield lost. Only, limited concentration of HMs are tolerable for plants, whereas higher concentration of these metals disrupted the metabolic and cellular activities of the plants. To overcome the toxicity of HMs, plants have a molecule name phytochelatins (PCs). PCs are important for HM detoxification and maintain the cellular integrity. They are prompted in plants in reaction to HMs management. It involved in metal chelation as well as metal sequestration in cytosol and vacuoles, respectively. With the major intend to increase the current knowledge of the topic, this review deals with PCs accumulation, mode of action and tolerance mechanism associated with HMs. This review aims to increase comprehension knowledge of PCs mediated remediation for the mitigation of HMs stress. PCs were investigated as novel molecules for further research and important clues for improving crop quality under stress.
Keywords: Phytochelatin synthase genes; Physiological functions; Stress tolerance